Sosialisasi Dan Edukasi Produk Perbankan Syariah Bagi Pelaku UMKM Tanah Grogot Kabupaten Paser - Wahyudi Wahyudi; Syifi Fauziyah; Rusmiati Rusmiati (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
The aim of the community service activity is "Socialization and Education of Sharia Banking Products for UMKM". This socialization aims to educate about sharia banking products so that they can know and understand sharia banking products so that it is hoped that a lot of knowledge and information will be absorbed by respondents, in this case are UMKM actors in Tanah Grogot. During educational outreach related to Sharia Banking, the team distributed questionnaires to respondents or participants in the socialization for UMKM actors to analyze based on the answers of respondents who attended the socialization. From the results of the socialization, the understanding of UMKM actors towards Islamic banks is sufficient. This can be proven by 15 respondents or (83.33%) who answered Yes, Fairly Understand. This shows that of the 18 UMKM actors who attended the socialization, they had sufficient understanding regarding Islamic banks and The Products. This means that the education that has been provided by the community service team has been quite successful in increasing the insight and knowledge of UMKM players and it is hoped that it can increase public awareness, especially UMKM players in Tanah Grogot, to carry out minimum savings transactions at sharia banks. Apart from that, one of the biggest obstacles in Sharia Bank transactions is the lack of available ATM networks, which makes UMKM players still hesitant to become interested in becoming Sharia Bank customers. This was proven by the UMKM players who attended the socialization, 9 respondents or 50% still Hesitance to become a sharia bank customer is due to the fact that the ATM network is not large, which is one of the factors why there are still many who are not interested in becoming sharia bank customers. From the results of the community service activity "Socialization and education of sharia banking products for UMKM in Tanah Grogot" it can be concluded that the presenters were able to educate the UMKMs who attended the socialization very well. This was proven by 11 respondents or 61.11% who responded that the material presented by the lecturers related to sharia banking product education was very good so that UMKM players could gain understanding and knowledge about sharia banking contracts and products which they hoped would be equipped with this knowledge. applied in sharia-based economic life.